The failure to obtain VC financing in the pre-start-up phase: Evidence from the Portuguese context - J. Bilau; E. Couto (South African Journal of Business Management, 2012)
In this paper, we contribute to the literature on access to venture capital during the pre-start-up phase of innovative firms by identifying the reasons for failing to obtaining formal VC according to nascent entrepreneurs. The main reasons cited for not obtaining venture financing were the small size of the VC market and limited public policies to support venture capital participation. The sub-sample of nascent entrepreneurs who based their financing proposals on more complete business plans included "lack of interest of the venture capitalists in pre start-up phase investments" as the number one reason.
Keywords: 650